REPRESENTASI ORANG BERIMAN DALAM KARTUN ANIMASI UPIN DAN IPIN EPISODE PUASA DAN ZAKAT FITRAH - Nanda Cita Aliffah (KOLONI, 2022)
Upin and Ipin is a cartoon originating from Malaysia which is very popular in its home country to Indonesia. This cartoon tells the story of two 5-year-old twins who live with their grandmother named Mak Uda or Opah and their older sister Ros. The Upin and Ipin cartoon is one of the cartoons that provide a lot of understanding about Islam to children, so it is the background to be used as an object of research. Upin and Ipin cartoons have episodes that describe the atmosphere of fasting and zakat fitrah. This study wants to understand the representation of believers in Upin and Ipin cartoons, fasting episodes, and zakat fitrah. The method of analysis used semiotic analysis of Roland Barthes. The research findings show that in the Upin and Ipin cartoons there are signs of believers, namely fasting and paying zakat fitrah. Keywords: Believers, Upin-Ipin, Fasting-Zakat Fitrah